Psychological responses and associated factors during the initial stage of the coronavirus disease (COVID-19) epidemic among the adult population in Poland - a cross-sectional study - Bernard Sozański; Agnieszka Ćwirlej-Sozańska; Agnieszka Wiśniowska-Szurlej; Krystian Jurek; Patryk Górniak; Karol Górski; Anna Englert-Bator; Lidia Perenc (BMC, 2021)
Abstract Introduction The study aimed to assess the emotional state, the occurrence of symptoms of depression, anxiety, and stress, as well as the quality of life of adults living in Poland during the first weeks of the COVID-19 pandemic. Method The study was conducted on a group of 700 people aged 18 and over living in Poland. An anonymous online questionnaire was used in this cross-sectional study. The psychological impact of COVID-19 was measured using the Revised Event Impact Scale (IES-R) and the Depression, Anxiety, and Stress Scale (DASS - 21). The quality of life was assessed using the WHOQOL-BREF. Results In Poland, a high average level of post-traumatic stress was found as a result of the COVID-19 pandemic, with at least the minimum level occurring in all surveyed people. There was also a high incidence of depression (48.00%), anxiety (39.29%), and stress (54.86) in the first phase of the pandemic. The average level of quality of life in Poland was the lowest for the physical domain and amounted to 49.56 (SD = 11.71). The standard of living in the psychological domain was 60.26 (SD = 13.14). Conclusions The pandemic is having a significant impact on human mental health. The very high average levels of post-traumatic stress, stress, anxiety, and depression as well as low quality of life make it necessary to consider interventions that will favor the use of more adaptive defense mechanisms and build mental resilience during an infectious disease pandemic and its long-term consequences.